Comparison of the 2002 and 2010 TNM classification systems regarding outcome prediction in clear cell and papillary renal cell carcinoma. Issue 2 (28th September 2012) - Pichler, Martin; Hutterer, Georg C; Chromecki, Thomas F; Jesche, Johanna; Kampel‐Kettner, Karin; Groselj‐Strele, Andrea; Hoefler, Gerald; Pummer, Karl; Zigeuner, Richard
<x xml:space="preserve">Abstract</x> Aims: A novel version of the tumour–node–metastasis (TNM) classification system for renal cell carcinoma (RCC) was introduced in 2010, although the prognostic significance with regard to different histological subtypes has not been explored. Therefore, the aim of our study was to compare the predictive ability of the 2002 and 2010 versions of the TNM classification system for clear cell and papillary RCC. Methods and results: Data from 2263 consecutive clear cell and 309 papillary RCC patients, operated at a single tertiary academic centre, were evaluated. According to TNM 2010, statistically significant differences for cancer‐specific survival (CSS) were observed for pT1a versus pT1b (P < 0.001) and pT3a versus pT3b (P < 0.004) in clear cell RCC; and pT1b versus pT2a (P = 0.002) and pT3b versus pT3c (P = 0.046) in papillary RCC. The c‐index for CSS in clear cell RCC was 0.74 and 0.73, and in papillary RCC 0.79 and 0.78, for the 2002 and 2010 versions of the TNM classification system, respectively. Conclusions: According to our data, the predictive ability of the 2010 version of the TNM classification system regarding CSS is not superior to the 2002 version, either in clear cell or in papillary RCC.